Integral Functionals of the Gasser–Muller Regression Function - Arabidze, D.; Babilua, P.; Nadaraya, E.; Sokhadze, G.; Tkeshelashvili, A. (Український математичний журнал, 2015)
For integral functionals of the Gasser–Muller regression function and its derivatives, we consider the plug-in estimator. The consistency and asymptotic normality of the estimator are shown. Для інтегральних функцiоналiв Функції регресії Гассера-Мюллера та їх похідних розглядається оцінка, що підключається. Встановлено обґрунтованість та асимптотичну нормальність цієї оцінки.